ANALISIS REAKSI PASAR PRA DAN PASCA PUBLIKASI UNQUALIFIED OPINION (Studi Pada Perusahaan yang Tergabung dalam Jakarta Islamic Index (JII) Tahun 2017-2019) - Lailatul Qomaria; Chasan Azari; Yanda Bara Kusuma (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2021)
The audit in financial statement is required to show the quality of financial statement in a company before being published on the market. The best audit opinion required by the market is the Unqualified Opinion, because it describes financial statement which is presented completely and independently from a material. The completeness of financial statement is very essential to provide a positive signal to the Market, so that the market place is able to give positive feedback. However, the market reaction is not always positive towards the Unqualified Opinion Publication. It is proven by the previous studies related to insignificant effect of Market Reaction toward Unqualified Opinion Publication. As the result, inconsistency is occured. Market Reaction can be measured by using Actual Return, Abnormal Return, and Trading Volume Activity toward Unqualified Opinion Publication. Furthermore, the study aims to find out the differences of Market Reaction before and after Unqualified Opinion Publication on Jakarta Islamic Index (JII) from 2017 to 2019. This is a Comparative Quantitative and Descriptive study with paired sample t- test for twenty days (ten days prior to publication and other ten days post-publication). The study takes the sample from ten companies that are suitable in term of the criteria. The result indicates insignificant difference of Market Reaction before and after Unqualified Opinion Publication in term of the significance value of Actual Return (0.835 > 0.05), Abnormal Return (0.122 > 0.05), and Trading Volume Activity (0.802 > 0.05). Thus, the overall significance value H0 is accepted, whereas, Ha is rejected. Moreover, mean of each variable shows a difference, however, it is categorized as low/ insignificant difference. After the hypothesis testing is applied, it reveals that there is no difference before and after Market Reaction of Unqualified Opinion Publication.